The acute effect of exercise intensity on free throws in young basketball players - Mokou, E.; Nikolaidis, P.; Padulo, J.; Apostolidis, N. (Sport Sciences for Health, 2016)
Purpose: Free throws (FT) accuracy is a major determinant of performance in basketball game. However, the effect of exercise intensities on FT accuracy has not been well studied. The aim of the present study was to examine the effect of different exercise intensities on FT accuracy in young male basketball players. Methods: For this aim, 22 basketball players (age 16.12 ± 1.16 years, body mass 76.4 ± 13.3 kg and height 186.4 ± 8.9 cm), classified into 2 age groups (younger 15.28 ± 0.48 years, n = 11; older 16.97 ± 1.00 years, n = 11). The participants performed 50 FT under five conditions (i.e. 10 FT per condition): after rest (A), after 3 min shuttle running with ~9 km h (B), ~9.5 km h (C), ~10 km h (D) and ~10.5 km h (E). Results: The analysis of variance showed a main effect of exercise intensity on FT accuracy ( p = 0.003, n = 0.585), heart rate (HR) ( p < 0.001, n = 0.990) and rate of perceived exertion (RPE) ( p < 0.001, n = 0.703): (a) FT accuracy in the C and D conditions was higher than the A condition ( p = 0.004); (b) all conditions differed for HR ( p = 0.047), the higher was the exercise intensity the higher was the HR, whereas no difference was revealed between D and E conditions; (c) the same trend as in the HR was observed in RPE (i.e. the higher the exercise intensity, the higher the RPE), too, where all conditions differed ( p = 0.047), except between C and D, and between D and E conditions. Conclusions: There was a significant exercise intensity × age interaction for RPE ( p = 0.011, n = 0.516), but not for FT accuracy ( p = 0.336, n = 0.224) or HR ( p = 0.128, n = 0.329). The findings of the present study showed that a minimum of exercise intensity was necessary to achieve peak FT performance and a shape of inverse U was suggested for the relationship between FT accuracy and exercise intensity. ABSTRACT FROM AUTHOR